2022
DOI: 10.3389/fnbot.2022.913052
|View full text |Cite
|
Sign up to set email alerts
|

Recent Machine Learning Progress in Lower Limb Running Biomechanics With Wearable Technology: A Systematic Review

Abstract: With the emergence of wearable technology and machine learning approaches, gait monitoring in real-time is attracting interest from the sports biomechanics community. This study presents a systematic review of machine learning approaches in running biomechanics using wearable sensors. Electronic databases were retrieved in PubMed, Web of Science, SPORTDiscus, Scopus, IEEE Xplore, and ScienceDirect. A total of 4,068 articles were identified via electronic databases. Twenty-four articles that met the eligibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 83 publications
0
20
0
Order By: Relevance
“…For predicting the coordination variability of the three CM directions, we constructed a deep-learning architecture with three layers of LSTM. Following the recommendation of previous research [ 63 , 64 ], we utilized the accelerometers’ raw acceleration data as feature data, which considerably aided our research ( Figure 5 , Figure 6 and Figure 7 ). The model predicts the coordination variability of three couplings in three CM directions with accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…For predicting the coordination variability of the three CM directions, we constructed a deep-learning architecture with three layers of LSTM. Following the recommendation of previous research [ 63 , 64 ], we utilized the accelerometers’ raw acceleration data as feature data, which considerably aided our research ( Figure 5 , Figure 6 and Figure 7 ). The model predicts the coordination variability of three couplings in three CM directions with accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…The impact shock has been discussed linked with the incidence of chronic overuse injuries ( Hennig et al, 1993 ). Given the advances of wearable technology in the past twenty decades, trial-axis acceleration and angular velocity could be measured from accelerometer and gyroscope in a single inertial sensor ( Afaq et al, 2020 ; Xiang et al, 2022d ; Xiang et al, 2022e ; Mason et al, 2023 ; Xiang et al, 2024 ; Yamane et al, 2024 ). This made segment acceleration measurements easier and more convenient, shifting the question to: Can we use portable and affordable inertial sensors to evaluate external loading rather than the force plate, which is conventionally embedded in the floor in a gait lab and is cost-prohibitive ( Sheerin et al, 2019 ; Hutabarat et al, 2021 ; Xiang et al, 2022e )?…”
Section: Introductionmentioning
confidence: 99%
“…One of the most significant advancements in biomechanics facilitated by wearable sensors is their capability to enable data-driven approaches, offering portable and innovative solution ( Halilaj et al, 2018 ; Gholami et al, 2020 ; Hernandez et al, 2021 ; Xiang et al, 2022e ; Mason et al, 2023 ; Xiang et al, 2023 ). Notably, the prediction of GRF metrics from inertial sensors using deep learning algorithms has shown high accuracy, as evidenced in studies ( Ngoh et al, 2018 ; Johnson W. R. et al, 2020 ; Tan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most researchers investigated particular ankle, knee, and hip moment in sagittal plane [12], hip moment in sagittal and frontal plane [29], hip moment in frontal plane [30], knee moment in sagittal [31] or frontal plane [13], ankle moment in frontal and sagittal planes [32], and lower limb joints moment in all three planes [18,33]. The previous studies utilized a few subjects and a recent review article by Xiang et al has shown to utilize more subjects (more than 20) [34] and we utilized 73 subjects. We estimated the power, which has been little done in previous research.…”
Section: Introductionmentioning
confidence: 99%